Probabilistic representation of quantum evolutions - Gikhman, Il. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A possibility of a choice of a complex phase space for the probabilistic representation of the solution of the Schrödinger equation has been given.